Potential Optimization of Industrial Waste as an Alternative Material for Composite Filler in Brake Pad Manufacturing – A Review - Sativa, Oriza; Nawangsari, Putri (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2024)
This study investigates the sustainable utilization of fly ash, palm slag and Cement By-Pass Dust (CBPD) waste as alternative materials for environmentally friendly brake pad development. These waste materials, with compositions similar to Asbestos, historically used in brake pad composites, present an eco-conscious solution. Integrating industrial waste in brake pad production offers substantial environmental benefits, technological progress, and commercial advantages. The compaction value and particle size distribution significantly impact brake pad mechanical properties. Adjusting these factors is crucial for meeting desired mechanical property requirements. A large particle size distribution enhances material density and hardness poses challenges in maintaining performance stability at high temperatures despite good recovery values. This paper highlights the potential of waste materials for sustainable brake pad development and underscores the need for careful optimization for high-temperature stability.